The level of declarative knowledge in Physical Education of students at institutions of higher education - Špehar, N. (Array, 2008)
Appropriate and continuous physical activity is necessary for a modern man. It significantly contributes to prevention of illnesses, improvement of health and is beneficial for many aspects of everyday life. Importance of adapting proactive life habits since childhood is reflected in behavior and quality of life during adulthood and that places a crucial responsibility upon the parents and teachers. Current studies on declarative level of knowledge indicate that sport and Physical education can improve active participation as well as passive interest in a particular sport. Physical education strives to improve motoric skills, expand interest, develop habit of independent exercise in free time and promote healthy life-style. Students show interest and curiosity, want to know how to shape up, reduce subdermal fat tissue, independently dose weight load, select specific physical exercise and plan appropriate nutrition. Providing the expert information based on kinesiological research can benefit the overall understanding of the problem, while theory and praxis of Physical education can further motivate and expand interest in regular exercise. The goal of this study is to establish the level of declarative knowledge in the area of Physical education which encompass several groups of questions: influence and importance of regular exercise on human body and health ; selecting weight loads ; nutrition ; rules and history of particular sport. Research was conducted on a sample of 439 college students attending the first three years in different science fields. Students anonymously participated in test of declarative knowledge consisting of 36 multiple-choice questions with five answers. Overall result of test is determined as the sum of correct answers. The results show insufficient knowledge in certain areas. Total number of correct answers is in range from 1 to 30. Questions in this test measure relatively different contents and that is reflected in Cronbach’ s test of reliability that yields value of 0, 595. Considering the fact that our intention was to measure knowledge in various different areas of Physical education, and healthy life habits, this value is considerate to be the appropriate. Theoretical lectures of Physical education, nutrition, maintenance of health as well as prevention of illnesses of locomotive system should become one of intervenient measures in promotion of health-related physical activity in order to expand the understanding and knowledge in this area. This test of declarative knowledge conducted on a sample of students in institutions of higher education shows current lack of adequate knowledge and necessity of additional education.